Teaching and learning experiences in Malaysian higher education: a case study of a teacher education programme - Tengku Kasim, Tengku Sarina Aini (Auckland University of Technology, 2012)
In line with its Vision 2020, the Malaysian education system is undergoing a significant pedagogical transition from a traditional teacher-centred to student-centred approach to teaching and learning. The Malaysian government expects these educational changes to occur in teaching and learning development in Malaysia’s secondary schools and in its higher education system. However, Malaysian research indicates that there is an on-going ambiguity in regard to the teaching and learning approaches adopted in Malaysian schools and in tertiary institutions. This seems to suggest that the introduction of Western concepts such as student-centred learning models brought about tension and conflict among Malaysian teachers and students. Moreover, previous Malaysian studies revealed that different cultures have different norms and values, and these cultural differences have a strong influence on educational practices. Therefore, there is a need to examine and develop appropriate pedagogies for the specific educational traditions, rather than assuming that Western ideas are effective and desirable in every context. Thus, the purposes of this study are to explore: (1) Malaysian teacher educators’ understanding about teaching, (2) Malaysian education students’ understanding about learning, and (3) the relationships between teacher educators and education students’ perceptions of teaching/learning and their actual teaching/learning practices. This research was conducted in a Malaysian university teacher education programme. It employed a case study using a qualitative approach with the adoption of several research methods: Individual interviews; focus group interviews; classroom observations; stimulated recall interviews; and document analysis. Involved in this study, were a total of seven teacher educators from differing backgrounds of teaching experience, and 12 final year education students. The major findings of the study are that: (1) The Malaysian teacher educator participants and the education student participants had adopted a combination of traditional teacher-centred and student-centred learning approaches because of the benefits that both approaches could offer to them, (2) The Malaysian teacher educator participants’ understanding of teaching and the education student participants’ understanding of learning were a reflection of their Islamic educational beliefs and philosophies, (3) The actual teaching/learning practices of the Malaysian teacher educators and the education student participants have been considerably influenced by their Islamic beliefs, (4) Several Islamic education philosophies are compatible with student-centred learning (Western learning models). (5) The learning perspectives of Malaysian Muslim students are influenced by their Islamic religion beliefs, thus differentiating them from other Asian learners (who have been found to exhibit Confucian values in the educational research literature). The findings of my research into Malaysian teachers and students result in understanding teaching/learning from a Malay Muslim viewpoint, distinguishing Malaysian teaching and learning for Malay Muslims from a Chinese Confucian standpoint. The research generates possible significant insight for other Muslim countries in the development of contemporary Islamic learning models. The findings of this study suggest that the Malaysian government and its policy makers should be more aware of the appropriateness or otherwise of the Western models for Malaysian education systems.
Keywords: Malaysian higher education; Teacher education programme; Qualitative study; Islamic learning theories; Constructivist learning theories; Student-centred learning